Objective evaluation of nasal breathing based on rhinomanometric data - Ерохин, Андрей Леонидович; Захаров, Игорь Петрович; Нечипоренко, Алина Сергеевна; Гарюк, Олег Григорьевич (Eastern-European Journal of Enterprise Technologies, 2014)
Currently, there are many objective diagnostic methods for nasal breathing difficulties. The main conventional method in otolaryngological practice is active rhinomanometry. The value of nasal resistance is considered as a diagnostic parameter of active anterior rhinomanometry. However, the results of the rhinomanometric measurements depend on race, age, gender, body mass index, and growth, etc. Thus, there is no evaluated criterion of physiological norm of nasal breathing according to the data from rhinomanometric studies. This fact significantly complicates the process of diagnosis and reduces diagnostic efficiency of rhinomanometry methods. For solving this problem, it is proposed to use additional spectral estimation data of the rhinomanometric studies using the modified covariance method. For this purpose, the spectral estimation software module is added to the software and hardware for rhinomanometric studies. The use of an advanced hardware and software system for rhinomanometric studies in clinical practice allows improving the diagnostic value of the active anterior rhinomanometry method.